Does Theory of Mind in Pre-kindergarten Predict the Ability to Think About a Reader's Mind in Elementary School Compositions? A Longitudinal Study. Issue 3 (26th May 2016) - Peskin, Joan; Comay, Julie; Chen, Xi; Prusky, Carly
Abstract : A critical skill in emergent writing is the developing ability to take the perspective of different readers; however, the precursors of this skill have not yet been identified. In this longitudinal study, 105 children (90 after attrition) were tested at 3 time points: pre-kindergarten (3–4 years old, n = 105), kindergarten (5 years old, n = 97), and Grade 1 (6–7 years old, n = 90). Theory of mind (ToM) in pre-kindergarten significantly predicted children's awareness of a reader's epistemic state when they dictated letters in both kindergarten and Grade 1 even after controlling for language (Peabody Picture Vocabulary Task [PPVT]) and inhibitory control. In addition, ToM in pre-kindergarten remained a significant predictor of reader awareness in Grade 1 after further controlling for reader awareness in kindergarten. There was little relationship between higher-order ToM tasks in kindergarten and reader awareness, but higher-order ToM in Grade 1 concurrently predicted reader awareness. Receptive vocabulary (PPVT) was significantly related to reader awareness at all time points, longitudinally and concurrently. This study has both theoretical implications for the relationship between ToM and emergent literacy and practical implications for the early identification and remediation of children at risk for later writing difficulties.